Horseradish peroxidase-labeled rabbit anti-non-structural protein 1 of dengue virus-2 for the diagnosis of dengue virus infections (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Early diagnosis of dengue virus (DENV) infection is essential for patient management and disease control. Detection of the antigen non-structural protein 1 (NS1) has been proven to provide early diagnosis of DENV infection. Thus, commercial NS1 antigen detection assays have been increasingly used and are becoming the tool of choice among clinicians to confirm DENV infection in Indonesia. METHODS To obtain anti-NS1 DENV antibody, NS1 protein (90 µg/ml) from the collection of the Department of Microbiology, Faculty of Medicine, Universitas Indonesia was injected into a rabbit. The anti-NS1 antibody from the rabbit was then labeled with horseradish peroxidase (HRP) using the periodate oxidation method. Sera were tested by enzyme-linked immunosorbent assay (ELISA) to detect NS1 from DENV-infected patients. RESULTS Serially diluted antibody labeled with HRP tested using the direct ELISA method showed the highest absorbance value at a 1:100 dilution (Mean [SD] = 1.35 [0.35]); even at a dilution as high as 1:3,200 (0.22 [0.15]), antibody labeled with HRP was able to detect the NS1 protein, although the absorbance value did not differ greatly from that of the negative control (0.13 [0.01]). CONCLUSIONS In an attempt to develop an NS1-based diagnostic test, polyclonal anti-NS1 DENV antibody was successfully produced as a diagnostic assay to determine the presence of DENV NS1 antigen in patients' sera.